2006
DOI: 10.5194/aab-49-55-2006
|View full text |Cite
|
Sign up to set email alerts
|

Some reproductive and growth traits of crossbred genotypes produced by crossing local sheep breeds of Kivircik x White Karaman and Chios x White Karaman in steppe conditions

Abstract: The aim of this study was to investigate some production traits of crossbred genotypes produced for lamb production by crossing local sheep breeds of Kivircik (K) x White Karaman (W) and Chios (C) x White Karaman in steppe conditions. W breed is raised in steppe conditions while K and C breeds are raised in Mediterranean climate conditions in Turkey. A total of 340 ewes was used through 3 years. 20.3, 19.6, 20.3 and 19.9 kg for weaning weight; 31.9, 29.4, 30.3, 30.5 and 30.1 kg for 180 day weight, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 6 publications
4
19
3
Order By: Relevance
“…They were similar to the values (30.4 and 31.9 kg) of 2 studies (19,20) conducted among lambs 6 months age. In different studies, differences between the LWs of lambs at 4 and 6 months of age could originate from differences in genetic capacity and climatic, maintenance, and feeding conditions.…”
Section: Live Weights Of Lambs At Day 120supporting
confidence: 74%
See 4 more Smart Citations
“…They were similar to the values (30.4 and 31.9 kg) of 2 studies (19,20) conducted among lambs 6 months age. In different studies, differences between the LWs of lambs at 4 and 6 months of age could originate from differences in genetic capacity and climatic, maintenance, and feeding conditions.…”
Section: Live Weights Of Lambs At Day 120supporting
confidence: 74%
“…The overall BW value of this study (4.1 kg) was higher than the values reported in some studies (10-12), but it was generally lower than the values indicated in many other studies (13)(14)(15)(16)(17)(18)(19)(20). A probable reason for low birth weights in the present study may be the high rates of twin births (18%-20%).…”
Section: Birth Weightcontrasting
confidence: 55%
See 3 more Smart Citations